(+)-Catechin inhibition of transmissible gastroenteritis coronavirus in swine testicular cells is involved its antioxidation. (December 2015) - Liang, Wulong; He, Lei; Ning, Pengbo; Lin, Jihui; Li, Helin; Lin, Zhi; Kang, Kai; Zhang, Yanming
ABSTRACT: Transmissible gastroenteritis virus (TGEV) causes transmissible gastroenteritis (TGE), especially in newborn piglets, which severely threatens the worldwide pig industry. In this study, (+)-catechin was evaluated for its antiviral effect against TGEV in vitro. Viability assays revealed that (+)-catechin treatment exerted a dose-dependent rescue effect in TGEV-infected ST cells, and this result was only obtained with the post-treatment application of (+)-catechin. The viral yields in (+)-catechin-treated cultures were reduced by almost three log10 units. Quantitative real-time PCR analysis of the TGEV genome revealed that TGEV RNA replication was restricted after (+)-catechin treatment. Intracellular reactive oxygen species (ROS) detection showed that (+)-catechin alleviated ROS conditions induced by TGEV infection. Our results showed that (+)-catechin exerts an inhibitory effect on TGEV proliferation in vitro and is involved its antioxidation. Highlights: (+)-Catechin has anti-TGEV effect. Anti-TGEV effect was working after TGEV infection. (+)-Catechin could relieve CPE caused by TGEV in ST cells. TGEV proliferation was decreased after (+)-catechin incubation. Antioxidation of (+)-catechin is related to its antiviral effect.